The importance of disaggregated data analysis of child undernutrition and its determinants - A district level analysis in the non-high focus state of India - P. Shirisha (Elsevier, 2022)
Background: Undernutrition persists to be a public health concern across several low and middle-income countries including India. However, the south Indian states- Kerala, and Tamil Nadu (TN) are recognized as "positive deviants" in terms of overall health outcomes including children's nutrition status. Hence, only a few studies have looked at trends of nutrition status in these states, especially at a disaggregated level. We aim to assess the progress made concerning children's (under 5) nutrition status and its determinants across the districts of a non-high focus state of TN. Method: We used data from district factsheets published by the National Family Health Survey-4 & 5 (conducted in 2015-16 and 2019-20 respectively) to calculate interval estimates of the prevalence of child undernutrition (stunting, wasting, and underweight) and its determinants for every district of TN. Result: Certain districts continue to bear a higher burden of undernutrition. The prevalence of child growth failure indicators was higher than the state average in Ariyalur, Dindigul, Erode, Karur, Trichy, the Nilgiris, and Sivagangai across both rounds of NFHS (4 as well as 5). Changes in immediate determinants were mixed across the districts. There was a consistent improvement in several underlying determinants - household assets, sanitation, and electricity - but to differing extents. Conclusion: In conclusion, the study reiterates the significance of understanding variations using granular data. Also, as the governments are increasingly focused on the progress of health outcomes at the district level. Our analysis provides timely evidence for policymakers to identify high-priority districts and design strategies to reduce the prevalence of undernutrition.